2015
DOI: 10.14746/ssllt.2015.5.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Global trends and local realities: Lessons about economic benefits, selves and identity from a Swiss context

Abstract: Inspired by the unexpected results of a standardized questionnaire survey of Swiss university students' motivation and attitudes toward English, the paper discusses the influence of global and local contexts on language learners' motivation and identity. As a result of the unprecedented spread of English as a foreign language (Crystal, 2003;Graddol, 2006), and, more importantly, the underlying social and economic issues that it reflects, elements of the global context intermingle with local realities to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…De Wit (2011) claims that the internationalization of universities are usually a good indicator of their quality (De Wit, 2011) and that, worldwide, the increase in the number of universities that offer EMI courses is more observed in the private sector (Kirkpatrick, 2014). Consequently, since very early ages, parents who can afford to, consider private English courses for their children aiming for the best universities and the possibility of living with international students in a culturally diverse environment (Csillagh, 2015). As pointed out by Finardi (2014) in relation to the role of English in private institutions in Brazil, the offer of English courses (be them in the form of general English courses or in the form of EMI courses) in the private sector, creates a social gap whereby only the economically privileged people can have access to this kind of knowledge and linguistic capital.…”
Section: Motivation To Internationalizationmentioning
confidence: 99%
“…De Wit (2011) claims that the internationalization of universities are usually a good indicator of their quality (De Wit, 2011) and that, worldwide, the increase in the number of universities that offer EMI courses is more observed in the private sector (Kirkpatrick, 2014). Consequently, since very early ages, parents who can afford to, consider private English courses for their children aiming for the best universities and the possibility of living with international students in a culturally diverse environment (Csillagh, 2015). As pointed out by Finardi (2014) in relation to the role of English in private institutions in Brazil, the offer of English courses (be them in the form of general English courses or in the form of EMI courses) in the private sector, creates a social gap whereby only the economically privileged people can have access to this kind of knowledge and linguistic capital.…”
Section: Motivation To Internationalizationmentioning
confidence: 99%
“…Therefore, Gardner's AMTB may be a better instrument, especially when supplemented with personal interviews. Csillagh's (2015) analysis of the Swiss context highlights important motivational factors in language learning, pointing out that "theoretical developments have gradually moved away from the notion of a clear-cut division between internal and external factors in favour of a more complex representation of L2 motivation" (p. 433). She found that different contextual elements play an important role in university students' motivation and attitude.…”
Section: Attitudes and Motivation In Fl Learningmentioning
confidence: 99%
“…In addition, depending on the research inquiry, a variety of research methodologies and methods are adopted: some take a quantitative approach (e.g. Csillagh, 2015), others employ a more qualitative oriented approach (e.g. Costa, 2015), while, still others adopt the mixed methods line of inquiry (e.g.…”
mentioning
confidence: 99%